School–university knowledge-exchange schemes (Research for All, 2018)
This article is based on an international study of knowledge-exchange schemes between schools and universities. It describes a number of such schemes in European countries, and offers practical suggestions about factors to be borne in mind when setting up a scheme. It combines the results of an online survey of 13 schemes in 6 EU countries and an analysis of 4 particular schemes in greater depth. The latter include a generic online space, a city-based forum, a university–school partnership and a rural collaboration on a specific issue. Based on these four cases, observations are made about factors that appear to help or hinder the interplay of knowledge exchange and practice improvement. A sequence of stages is suggested to describe the process.